HELIUM SIGNATURE OF THE SUBCONTINENTAL LITHOSPHERIC MANTLE - Gautheron C.; Moreira M. (My University, 2002)
Peridotites and basalts from continental areas over the world show a helium isotopic ratio that is relatively homogeneous and more radiogenic than the MORB source. The mean ratio is 118#000+/-15#500 (R/Ra=6.1+/-0.9), compared to the MORB source ratio of 90#000+/-10#000 (R/Ra=8+/-1). This rather constant ratio indicates that the effect is worldwide and can be directly bound to subcontinental mantle geodynamics. A closed system model would imply low uranium content in the subcontinental mantle (<2 ppb), disagreeing with the measured u concentrations in continental mantle peridotites (4-40 ppb). this study, we evaluate a model where lithospheric is steady state for helium. helium residence time subcontinental can therefore be estimated and gives values around 100 ma, compatible plate tectonic scales melt fluxes through lithosphere. however, predicts 3He fluxes between 110 and 1000 mol/yr depending on different U contents and depth of the lithosphere. This appears much higher than the flux observed in continental areas.
Keywords: MANTLE; NOBLE GASES; HELIUM; STEADY-STATE PROCESSES; MODELS; XENOLITHS